PENGGUNAAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS SISWA PADA KELAS V SDN 028229 BINJAI BARAT - Haris Suwondo; Dede Ruslan; Anita Yus (JURNAL TEMATIK, 2019)
"> This study aims to know the use of genius learning strategies to increasestudents' motivation and social studies learning outcomes in the fifth grade of SDN028229 West Binjai. This type of research is classroom action research (CAR). Theresults of this study are in the first cycle of students who succeeded as many as 10 people(40%) and students who have not completed as many as 15 people (60%) with an averagescore of 62.8. Students who have received good grades on aspects not quickly satisfiedwith the achievements that have been achieved amounted to 166 students with apercentage of 64%, it shows the level of student motivation is low. In the second cycle asa whole students complete 100% with an average value of 75.8. Some indicators thatexperienced an increase in motivation from the 14 existing indicators received apercentage of ≥80% and received a very good predicate. Thus the use of genius learningstrategies can increase the motivation and results of social studies learning of students inclass V SDN 028229 West Binjai